2020
DOI: 10.3389/fphys.2020.573325
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Paced Breathing and Autonomic Function in People Post-stroke

Abstract: Purpose: To determine if acute slow breathing at 6 breaths/min would improve baroreflex sensitivity (BRS) and heart rate variability (HRV), and lower blood pressure (BP) in adults after stroke.Methods: Twelve individuals completed two randomized study visits where they performed a 15-min bout of breathing exercises at 6 breaths/min (slow) and at 12 breaths/min (control). Continuous BP and heart rate (HR) were measured throughout, and BRS, BRS response to elevations in blood pressure (BRSup), BRS response to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Lachowska et al reported that HR and blood pressure responses decreased considerably with slow breathing exercises in heart failure patients with reduced ejection fraction and enhanced a variety of health-related scores of quality of life (QoL) [ 70 ], while another study exhibited improvement in the long-term cardiorespiratory capacity of these patients [ 71 ]. Post-stroke patients also seem to benefit from slow breathing, with increased baroreflex sensitivity, lower systolic blood pressure, and HR with increased HRV [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lachowska et al reported that HR and blood pressure responses decreased considerably with slow breathing exercises in heart failure patients with reduced ejection fraction and enhanced a variety of health-related scores of quality of life (QoL) [ 70 ], while another study exhibited improvement in the long-term cardiorespiratory capacity of these patients [ 71 ]. Post-stroke patients also seem to benefit from slow breathing, with increased baroreflex sensitivity, lower systolic blood pressure, and HR with increased HRV [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study using intracranial electroencephalogram demonstrated respiration-locked oscillations during attentive breathing (mindful breathing) with stronger power in the anterior cingulate cortex, premotor cortex, insula, and hippocampus (Herrero et al, 2018 ), which are regions supposed to be involved in executive function (Carter et al, 1999 ; Rizzolatti et al, 2002 ; Eichenbaum, 2004 ). SLOW (device-guided, 5–6 breaths/min) is currently a Federal Drug Administration-approved treatment indicated by the American Heart Association for relaxation (Larson et al, 2020 ). Generally, for a healthy person, increased heart rate variability (HRV) indicates a relaxed state.…”
Section: Introductionmentioning
confidence: 99%